2019
DOI: 10.3390/ijerph16214077
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative/Antioxidative Status in Patients after Myocardial Infarction and in Those without Cardiovascular Event Depending on Anthropometric Factors Defining Body Weight

Abstract: Obesity is one of the factors leading to the development of atherosclerosis. This metabolic disorder is associated with an increased production of reactive oxygen species, which affect the oxidative stress levels. The aim of this study was to evaluate oxidative/antioxidative status and to investigate the correlation between redox markers and anthropometric parameters and body composition in adult patients after myocardial infarction and in individuals without a cardiovascular event in the past. Descriptive dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 80 publications
(87 reference statements)
0
4
0
Order By: Relevance
“…OSI is the percentage ratio of TOS to TAC. In a study by Nowicki et al, in which people after cardiovascular events (study group) and those without a history of cardiovascular events (control group) participated, no significant difference was found in OSI between the research and the control group, as well as no significant correlation was found between OSI and BMI [ 45 ]. Our study also showed no significant difference in terms of OSI between the MUO, MHO, and MHNW groups.…”
Section: Discussionmentioning
confidence: 99%
“…OSI is the percentage ratio of TOS to TAC. In a study by Nowicki et al, in which people after cardiovascular events (study group) and those without a history of cardiovascular events (control group) participated, no significant difference was found in OSI between the research and the control group, as well as no significant correlation was found between OSI and BMI [ 45 ]. Our study also showed no significant difference in terms of OSI between the MUO, MHO, and MHNW groups.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, young smokers diagnosed with acute myocardial infarction, had significantly higher OSI and TOS levels and lower TAS and LOOH levels. Moreover, CAD severity correlated positively with OSI and TOS levels, suggesting that high levels of OSI and TOS could be considered as indicators of disease severity and heavy smoking-related vascular damage in early-onset CAD [119,157]. Finally, Frati et al showed that smokers had an increase in oxidative stress markers and a worsening of antioxidant systems compared to non-smoker [161] (Table2).…”
Section: Smokingmentioning
confidence: 98%
“…Hypertension is one of the most common cardiovascular risk factors, and oxidative stress is important in the molecular mechanisms associated with it [162]. Oxidative stress was observed among hypertensive patients as depicted by the high plasma levels of oxLDL [107,114,119], and reduced enzymatic antioxidant activity, which is determined by glutathione peroxides (GPx) [110,114], total antioxidant capacity (TAOC) [113], ferric reducing ability of plasma (FRAP) [113], total antioxidant capacity (TAC) [115,119]. There are many studies focusing on the comparison of oxidative stress biomarkers in hypertensive patients.…”
Section: Hypertensionmentioning
confidence: 99%
“…21,24 The relation between BMI and oxidative stress has been reported. 25,26 Low-density lipoprotein-cholesterol-C level is not a criterion for MetS and is not necessarily elevated in MetS patients, 27 but risk is further increased by elevated LDL-C in patients with MetS. 28 In the present study, LDL-C levels were significantly higher in the MetS group than in the controls.…”
Section: Discussionmentioning
confidence: 45%